Design quality of freshwater lobster farming in Teluk Intan / Aman Faizal Khalili, Ar. Ts. Amir Sheriff Mohd Sheriff and Dr. Zalina Samadi - Khalili, Aman Faizal; Mohd Sheriff, Amir Sheriff; Samadi, Zalina (College of Built Environment, 2023)
Perak River is the second longest river in Peninsular Malaysia, after Pahang River. With a total length of 420 km, Perak River is a unique river system as it is the only river in Malaysia that has four consecutive hydroelectric dams, namely Temengor, Bersia, Kenering and Chenderoh.